Kontinuální vzdĕlávání lékárníků v Ceské Republice. 2. Cyklus 2002-2005 - Kolár, J; Nováková, J (Ceska a Slovenska farmacie, 2006)
The paper deals with continuous education of pharmacists in the Czech Republic in 2002-2005 (2nd cycle). It surveys the seminars organized within the framework of continuous education, their number, topics, and lecturers. A total number of 232 professional seminars took place, which included 339 lectures, mainly on pharmacology (76.1%).
Keywords: kontinuální vzdělávání farmaceutů; Education, Pharmacy, Continuing; Česká republika; Czech Republic